Poetic film lattice in the wolf poem of Bohtari (Journal of the College of Basic Education, 2022)
The Arabic poem is homogenous, although it is traditional with cinematic art. The hypothesis of impact and impact between them, because the most influential texts are carrying in the scenes of the shot through which the reader can imagine the space of the image and events, so the poetry of the shot was one of the most attractive contexts in poetry. Hence the study was based on the descriptive method - analytical, to apply the vision of the poetic bacterial through cinematic technologies. Al-Bahtari's approach to the wolf's poem has made the recipient enter the world of cinematic narrative, because it is mixed with a poetic spirit and a cinematic vision that is far from ambiguous. This research came in a set of specific contexts that can be shared between the poet and cinema technician first, the sizes of the shots, shooting angles, camera movements, and finally the chromatic rhythm , and this research has come to a number of critical results that represent the reality of technical interaction between Technicians, then followed by sources and references.